2022
DOI: 10.1016/j.coche.2021.100764
|View full text |Cite
|
Sign up to set email alerts
|

Plasma for biomedical decontamination: from plasma-engineered to plasma-active antimicrobial surfaces

Abstract: Modern society is suffering from many infectious microbes. Developing antimicrobial surfaces for biomedical decontamination and sterilization is one of the strategic solutions to mitigate the spread of infectious pathogens. Here, we outline the paradigm of plasmas for biomedical decontamination by presenting approaches of plasmaengineered antimicrobial surfaces and novel plasma-active antimicrobial surfaces. Low-temperature plasma can not only be used as a material fabrication tool for antimicrobial surface en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…At the same time, it will have a chemical reaction to produce ozone, nitrogen dioxide, nitric oxide, etc., accompanied by high-frequency pulse current and objective energy loss. In the application of corona discharge in the customization of materials, it can be seen that plasma-generated short-lived reactive oxygen and nitrogen species (RONS) are believed to be key agents for the variety of microorganisms [20].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it will have a chemical reaction to produce ozone, nitrogen dioxide, nitric oxide, etc., accompanied by high-frequency pulse current and objective energy loss. In the application of corona discharge in the customization of materials, it can be seen that plasma-generated short-lived reactive oxygen and nitrogen species (RONS) are believed to be key agents for the variety of microorganisms [20].…”
Section: Discussionmentioning
confidence: 99%
“…The products generated from the precursor-plasma reactions, such as reactive plasma species, as well as non-reactive species, deposit on the substrate, where the adsorption and surface reactions take place simultaneously. Some of the published results have been reviewed here [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were made for the portion of electric fields to the effects observed. Many studies have revealed and summarized the antimicrobial effects of gas plasma-derived ROS [ 17 , 18 ]. This was found mainly by adding antioxidant molecules or enzymes, such as N-acetylcysteine and catalase, to the samples, finding that many of the gas plasma-derived effects were reversed.…”
Section: Introductionmentioning
confidence: 99%